Penerapan Digital Branding UMKM Dapur Gemilang Fitriyah Melalui Komunikasi Visual - Sufi Hamzah F; Anjelina Sugianti; Adella Ratna Nur Dianti; Mei Retno Adiwaty (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
In the era of the industrial revolution 4.0, technological developments underwent very rapid changes so that the information obtained was quite easy and fast to obtain. The marketing system is no exception. Digital marketing currently has a big influence on sales. The MSME Kitchen Gemilang Fitriyah is an MSME engaged in the culinary business in Penjaringansari Village, Rungkut, Surabaya. In this case, MSME actors still have problems in that their products do not have an inherent brand image, and do not have social media to expand their market. Through the use of digital branding by loading visual communication, it is hoped that it will be able to help MSME actors, as one of the promotional media to develop a business in the digital marketing era. The method used in this research is to use a qualitative method with a descriptive approach. In the data collection stage using direct interviews with MSME owners. From the results of this study resulted that by choosing social media as promotional media and making logo designs, packaging labels, and product photos to develop their MSME.